Knowledge and attitudes on contraceptives among undergraduates in the state universities of the Western Province - Upuli Perera; chrishantha Abeysena (College of Community Physicians of Sri Lanka, 2019)
Objective: To describe knowledge and attitudes on contraceptives among undergraduates in the state universities of the Western Province Methods: A descriptive cross sectional study was conducted among 1575 second and third year undergraduates using stratified cluster sampling of the selected universities. A pre-tested self-administered questionnaire was administered to assess knowledge and attitudes on contraceptives. Scores were given. Percentage of knowledge and attitude categories was calculated. The associations of knowledge and attitude categories with selected variables were assessed. Results: Only 28.4% (n=447) had good knowledge on contraception while 27.3% (n=430) had satisfactory knowledge and 44.3% (n=698) had poor knowledge. Students who studied in Bio-Science streams showed higher percentage of (71%, n=176) good knowledge than the non-Bio-Science streams (20.2%, n=271) (P<0.001). Males (31.0%, n=200) reported more good knowledge than females (26.6%, n=246) (P<0.05). A majority (52.9%, n=833) of undergraduates had poor knowledge on condoms while 26.2% (n=412) had satisfactory knowledge and 21% (n=330) had good knowledge. Male (41.2%, n=266) had more good knowledge on condoms than females (6.9%,n=64) (P<0.001). Good knowledge on condoms was higher among those who have studied at non-mixed schools (28.3%, n=154) and who have studied in Bio-Science stream (29.0%,n=72). Around one third (30.5%, n=477) of undergraduates had desirable attitudes and 69.5% (n=1089) had undesirable attitudes on contraception. Males (37.3%, n=239) had more desirable attitudes than females (25.6%, n=236) (P<0.001). Undergraduates those who had studied in Bio-Science stream (38.2%, n=94, P=0.004) had more desirable attitudes than non-Bio-Science stream. A majority (61.2%, n=957) of respondents had undesirable and 38.8% (n=608) had desirable attitudes on male condoms. Males (58%, n=358) had more desirable attitudes than females (27.1%, n=250) (P<0.001). Conclusion: Good knowledge and desirable attitudes on both contraceptives and condoms were less among undergraduates.